Effect of regrouping unfamiliar pigs at weaning on immune function - Blecha, Frank; Pollmann, D.S.; Nichols, David A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pigs weaned at 3 weeks of age and regrouped with unfamiliar individuals had a 4-fold increase in plasma cortisol when compared to pigs that remained in a litter group. However, cellular measures of immune function were not altered by regrouping.
Keywords: Swine; Weaning; Immunity